Priority setting for conservation in south-west Cameroon based on large mammal surveys - Forboseh, P.F.; Eno-Nku, M.; Sunderland, Terry C.H. (2007)
The forests of the Cameroon-Nigeria transboundary region have been highlighted as a high conservation priority, yet many of the extant forest remnants remain relatively unknown, particularly with regard to the occurrence of large mammals. Between 2002 and 2004 the authors surveyed the large mammal fauna of the Mone and Ejagham Forest Reserves and the Upper Banyang, Nkwende Hills and Etinde forests of southwest Cameroon. The objective was to document the extant large mammal species as an important step in the review of government priorities to identify key sites within the region for conservation and management. The authors reviewed the available literature on mammal distribution and then surveyed the forests for mammal and human signs. Despite a growing illegal commercial trade in wildlife, particularly for bushmeat, many sites retain populations of one or more threatened and locally rare large mammal species of significant conservation importance. Moreover, the sites collectively complement each other in terms of their representation of the threatened large mammal fauna. An emphasis on the enforcement of wildlife legislation and minimizing logging impact are of primary importance for the conservation of large mammals in these and other forest remnants in south-west Cameroon. In addition, at some sites, there already exists community interest in active wildlife management.